Pengaruh Persepsi Pelaku Usaha Mikro Kecil Menengah Tentang Akuntansi, Pengetahuan Akuntansi, Dan Skala Usaha Terhadap Penggunaaan Informasi Akuntansi Di Kabupaten Gresik - Maghfiroh, Nur Lailatul; Sholichah, Mu'minatus; Umaimah, Umaimah (Universitas Muhammadiyah Gresik, 2024)
This study aims to examine the effect of micro, small and medium business actors' perceptions of accounting, accounting knowledge, and business scale on the use of accounting information in Gresik Regency. This study examines accounting information on Micro, Small and Medium Enterprises (MSMEs) in Gresik Regency using independent variables, namely the perception of micro, small and medium enterprises about accounting, accounting knowledge and business scale. The research population is MSMEs registered at the Department of Cooperatives and Trade of Gresik Regency. Sampling using the purposive sampling method with a total sample of 100 respondents. Data collection is done by sending a questionnaire via broadcast messages in the form of google from. The data analysis technique used is multiple linear regression analysis. The results of hypothesis testing indicate that the perception variables of micro, small and medium enterprises about accounting, accounting knowledge and business scale have a significant and significant effect on the use of accounting information. Based on these results, the Office of Cooperatives and SMEs are expected to be able to carry out regular counseling to MSMEs in order to improve the quality of human resources and individual understanding in order to develop their business, because by increasing these three variables it can develop and optimize users of accounting information that is useful for developing their business.